Pater the classicist : classical scholarship, reception, and aestheticism - Evangelista, Stefano; Evangelista, Stefano; Martindale, Charles; Martindale, Charles; Prettejohn, Elizabeth; Prettejohn, Elizabeth (Classical presences, 2017)
'Pater the Classicist' is the first book to address in detail Walter Pater's important contribution to the study of classical antiquity. The contributions presented here discuss his classicism generally, his fiction set in classical antiquity, his writings on Greek art and culture, and those on ancient philosophy